The Witch King - Edgmon, H. E. (Inkyard Press, 2021)
Wyatt, a transgender witch, hides in the human world after he loses control of his magic, but his fiancé, Emyr, a fae prince, is at risk of losing his throne if he does not find and marry Wyatt.